In between : the art project of Expo 2000. - Butzer, André; Dickhoff, Wilfried; Groos, Ulrike; Höller, Carsten; König, Kasper; Liebs, Holger; Oehlen, Albert; Signer, Roman; Trockel, Rosemarie; Waldvogel, Florian; West, Franz; van Warmerdam, Marijke (Köln : DuMont Verlag, 2000)
Höller, Carsten ; Trockel, Rosemarie ; Signer, Roman ; McCarthy, Paul ; Gelatin ; van Warmerdam, Marijke ; Cattelan, Maurizio ; Oehlen, Albert ; West, Franz ; van der Stokker, Lily ; Rehberger, Tobias ; Orozco, Gabriel ; Sone Yutaka ; Branca, Glenn ; Oursler, Tony
Engels
In between, the art project of Expo 2000, Expo 2000, Köln, 1 June - 31 October 2000
boek